Ubiquitin and ubiquitin-like conjugation systems in trypanosomatids. (December 2022) - Burge, Rebecca J; Mottram, Jeremy C; Wilkinson, Anthony J
Abstract : In eukaryotic cells, reversible attachment of ubiquitin and ubiquitin-like modifiers (Ubls) to specific target proteins is conducted by multicomponent systems whose collective actions control protein fate and cell behaviour in precise but complex ways. In trypanosomatids, attachment of ubiquitin and Ubls to target proteins regulates the cell cycle, endocytosis, protein sorting and degradation, autophagy and various aspects of infection and stress responses. The extent of these systems in trypanosomatids has been surveyed in recent reports, while in Leishmania mexicana, essential roles have been defined for many ubiquitin-system genes in deletion mutagenesis and life-cycle phenotyping campaigns. The first steps to elucidate the pathways of ubiquitin transfer among the ubiquitination components and to define the acceptor substrates and the downstream deubiquitinases are now being taken. Highlights: Ubiquitination and ubiquitin-like modification regulates trypanosomatid differentiation. Inventories of ubiquitination system components compiled for trypanosomatids. Essential components of ubiquitination systems established by deletion mutagenesis. Challenge to define pathways of ubiquitin transfer and acceptor substrates.